1978
DOI: 10.1001/archderm.114.3.382
|View full text |Cite
|
Sign up to set email alerts
|

Diaper area granuloma of the aged

Abstract: Nine women, aged 77 to 89 years, suffered from diaper dermatitis, and many granulomas were seen in the genital or gluteal region restricted to the lesion of dermatitis. Because these granulomas resembled granuloma gluteale infantum of Tappeiner and Pfleger, we propose to call this condition diaper area granuloma of the aged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Histology shows dermal oedema, a dense granulomatous infiltrate of plasma cells and lymphocytes, together with fibrinoid necrosis and deposition of haemosiderin. Similar cases have been reported in incontinent elderly women, in whom corticosteroids were not a factor (Maekawa et al 1978). Treatment is withdrawal of topical steroids if relevant and any occlusive factors must be minimized.…”
Section: Infantile Gluteal Granulomasupporting
confidence: 65%
“…Histology shows dermal oedema, a dense granulomatous infiltrate of plasma cells and lymphocytes, together with fibrinoid necrosis and deposition of haemosiderin. Similar cases have been reported in incontinent elderly women, in whom corticosteroids were not a factor (Maekawa et al 1978). Treatment is withdrawal of topical steroids if relevant and any occlusive factors must be minimized.…”
Section: Infantile Gluteal Granulomasupporting
confidence: 65%
“…But Maekawa et al (9) reported that it also appears in aged women wearing diapers. The clinical picture of our case was completely different from that of granuloma gluteale infantum, but the histological findings, marked acanthosis and dense inflammatory infiltrates in the dermis, were similar.…”
Section: Commentmentioning
confidence: 99%
“…In these cases the condition has been referred to as diaper area granuloma of the aged or granuloma gluteale adultorum. 8,9 Lesions are similar to those seen in infants, typically being firm, reddishpurple, oval, or elongated nodules and plaques in the pubic area, scrotum, buttocks, and medial aspects of the thighs. 3,5,20 Granuloma gluteale has a somewhat nonspecific histology.…”
Section: Discussionmentioning
confidence: 92%
“…Similar lesions may also be seen in adults. 8,9 Although it has persisted in the literature, the term ''granuloma gluteale'' is a misnomer, as the condition is not granulomatous on histologic examination. Pseudoverrucous papules and nodules (PPPN) is a rare condition that was first reported in association with urostomy sites.…”
mentioning
confidence: 99%